Tingkuluak Payakumbuh Dalam Karya Digital Painting - Aulia Reski Wizla; Suib Awrus (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this final project is to create digital paintings with ideas sourced from the Tingkuluak of Payakumbuh. Tingkuluak is a head ornamentation worn on wrapped cloth, typically by Minangkabau women. The existence of Tingkuluak is fading, and its significance is largely unknown. Limited information is available regarding its use, meaning, and philosophical explanations. Hence, this final project aims to present the Tingkuluak cultural heritage through digital paintings, with the main subject being the Tingkuluak itself. The creation method involves five stages: preparation, which includes observation; followed by in-depth analysis, referred to as elaboration; then the synthetic stage involving idea formulation and concept realization. The author utilized the Ibis Paint X application accessed through a tablet device for the creation process. The author produced 10 digital artworks with the following titles: "Uni Bakompong Koto Nan Ampek," "Uni Bakompong Koto Nan Gadang," "Mintuo Nan Alah Baminantu Jo nan Bukan," "Manjapuik Minantu," "Jan Digaduah," "Bundo nan Taat," "Gadih Ikek," "Duo Koto," and "Bundo Si Anak Daro."